El Excentrico, 1961-08-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 5, 1961 [5 de Agosto de 1961]. Ano 11, No 20. Cover has a photographs of nine couples from San Felipe's Formal Dance with headline, "Review of Club San Felipe's Formal Dance."